Of persons and organisms: a reply to Howsepian - Lockwood, M. (Journal of medical ethics, 1997)
Howsepian has presented a number of thought experiments, which are designed to undermine my claim that our identity through time is grounded in the continued existence of those structures in our brains which directly underlie mental functioning. I argue that the conclusions which Howsepian draws from these thought experiments are mistaken, and that his discussion of them is vitiated, in particular, by his failure to distinguish between personal identity and the identity of the associated human organism.